The Value Chain of Locally Grown Japonica Rice in Mwea, Kenya - Mamoru Watanabe; Yutaka Sumita; Issaku Azechi; Kengo Ito; Keigo Noda (Agriculture, 2021)
In Kenya, there is an urgent need to strengthen domestic rice production to improve food security. To achieve this, it is necessary to develop a value chain of competitive rice varieties that creates new value over and above that of conventional varieties. In this study, we focused on locally grown japonica rice produced in the Mwea area, which has recently begun to be distributed in Nairobi. Through interviews with Japanese restaurants, Japanese food stores, and consumers as well as interviews with stakeholders in the value chain the market price, consumer acceptability, and profitability of locally grown japonica rice were determined. We evaluated the value chain of locally grown japonica rice based on the interaction between the potential demand and a value chain analysis and examined improvement measures to establish the value chain. The results showed that 76% of consumers who eat staple foods other than rice rated locally grown japonica rice as “very good” or “good”, indicating that it may be acceptable to those who do not usually eat rice. The net profits for locally grown japonica rice were higher than those of conventional rice at the production, processing, and distribution stages, which is an advantage for producers and demonstrates that the elimination of middlemen is effective and highly profitable for each stakeholder. In contrast, the consumer price of locally grown japonica rice was higher than that of conventional rice, indicating that some challenges remain to be overcome. Our estimation approach will allow further study of target values such as selling price in other desired value chains. Together, our findings suggest the potential of the locally grown japonica rice value chain to contribute to the strengthening of domestic rice production.